2020
DOI: 10.1038/s41598-020-71374-3
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoproteomics gives new insight into early southern African pastoralism

Abstract: The advent of domestication is a major step that transformed the subsistence strategies of past human societies. In Africa, domestic caprines (sheep and goat) were introduced in the northeastern part of the continent from the Near East more than 9000 years ago. However, their diffusion southwards was slow. They are thought to have made their first appearance in the southern part of the continent ca. 2000 years ago, at a few Later Stone Age sites, including Leopard Cave (Erongo region, Namibia), which provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 68 publications
1
26
1
Order By: Relevance
“…The consensus springbok collagen sequences that we present differ from those shown in supplementary Fig. S1 of Le Meillour et al (2020) 24 . That figure shows the GE P GP V GAVGPAGAVGPR (corresponding caprine ortholog of the m/z 1532 marker) as present in springbok alpha 2 chain of collagen type 1.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…The consensus springbok collagen sequences that we present differ from those shown in supplementary Fig. S1 of Le Meillour et al (2020) 24 . That figure shows the GE P GP V GAVGPAGAVGPR (corresponding caprine ortholog of the m/z 1532 marker) as present in springbok alpha 2 chain of collagen type 1.…”
Section: Discussioncontrasting
confidence: 75%
“…Recent biomolecular studies at other archaeological sites in this part of the world have shown that some putative early domesticates are actually wild species 24 ; see also 16 – 18 . The winter rainfall climate of south-western Africa precluded the spread of African grain crops (principally sorghum and millets) into the region, so that agriculture was practised only after European colonisation in the seventeenth century CE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These issues often render their bones indistinguishable from one another, and from other similar-sized wild bovids (e.g. [ 39 , 40 ]). To address this issue, this paper uses the biomolecular method of collagen fingerprinting to identify caprines to species level at eight archaeological sites across island eastern Africa.…”
Section: Introductionmentioning
confidence: 99%